Promotion as the Cause of Crises - England, Minnie Throop (Quarterly Journal of Economics, 1915)
Two groups of crisis theories, 748. — Failures the chief phenomena in the crisis, 749. — Promotion activity the cause of prosperity, 750. — Relation between promotion and failures, 752. — Newly-promoted concerns fail, 752. — Old concerns fail because of competition of new, 755. — All kinds fail because of inability to cope with dynamic conditions, 756. — The part of credit in the cycle, 761. — Exhaustion of loanable funds, 761. — Falling reserve ratios or falling reserves, 762. — Gold movements before crises, 763. — Break down of credit not the main cause of crises, 764. — Crisis failures include insolvent as well as solvent concerns, 765. — Promotion the cause of crises, 766.